Intensification of Educational-Cognitive Activity of the Future Primary School Teachers During Lectures on Pedagogy - Halyna Dudchak (Pedagogical Discourse, 2017)
Іn the article the author clears out the essence of a lecture as an organizational form of teaching in higher educational institutions, the requirements to its content and methods of implementation have been outlined. The content of the notion «intensification of educational-cognitive activity» has been revealed. The ways of intensification of educational-cognitive activity of the future primary school teachers in the process of lecturing on pedagogy have been identified.It was found out that the implementation of the studied problem promotes the use of such types of lectures as a problem lecture, lecture-visualization, pre-planned lecture errors, lecture-dialogue, lecture-press conference. To a large extent the intensification of educational-cognitive activity of students in the course of study pedagogy allows the use of methods such as playing techniques, the method of «analysis of specific situation» the problem method, brainstorming, method of teaching discussion. To the effective ways of intensification of educational-cognitive activity of the future primary school teachers at lectures on pedagogy belong pedagogical management of educational- cognitive activity of students, organization of various types and forms of independent work of students, use of videos, appeal to the life experience of students, using examples from the experience of work of pedagogues-classics and practicing teachers, realization of intra-subject connections, use of certain methods of securing educational material, emotional teaching of educational material.